1874
DOI: 10.1002/cber.187400702232
|View full text |Cite
|
Sign up to set email alerts
|

Ueber das atmosphärische Wasserstoffhyperoxyd

Abstract: erhalten haben. Die Reaction ist sehr glatt und man erhalt beinahe die theoretische Menge. Das Phosphin ist eine farblose bei 216 bis 220° siedende, stark riechende Flcssigkeit yon basischen Eigenschaften. K a r l s r u h e , December 1874. 487. Em. Schone: Ueber das atmospharische Wasserstoffhgperoxgd. ( V orliiu fig e M i t t he i l u ng.) (Eingegangen am@ December; verlesen in der Sitzung von Hrn. Oppenheim.) G. M e i s s n e r ' ) , S c h o n b e i n z ) , H. S t r u v e 3 ) , W e r n e r S c h m i d 4 ) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1896
1896
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Tetraalkylleads, which may form a small portion of the total lead emitted from automobiles and from related industries (1-3), are volatile but environmentally labile. They are degraded abiotically (4)(5)(6) and via metabolic processes (7,8) to result, sequentially, in trialkyllead (R3Pb+), dialkyllead (R2Pb2+), and inorganic lead (Pb2+) salts. Ionic alkyllead salts are considered to be more persistent in the environment, and they retain much of the acute toxicity of their tetraalkyl progenitors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tetraalkylleads, which may form a small portion of the total lead emitted from automobiles and from related industries (1-3), are volatile but environmentally labile. They are degraded abiotically (4)(5)(6) and via metabolic processes (7,8) to result, sequentially, in trialkyllead (R3Pb+), dialkyllead (R2Pb2+), and inorganic lead (Pb2+) salts. Ionic alkyllead salts are considered to be more persistent in the environment, and they retain much of the acute toxicity of their tetraalkyl progenitors.…”
Section: Introductionmentioning
confidence: 99%
“…In 1874, Schóne reported that H202 was present in rainwater (5). Since then, hydrogen peroxide concentrations as high as 60 µ for rainwater and 250 µ for cloudwater samples have been reported (6)(7)(8).…”
mentioning
confidence: 99%